Regulation of Dendritic Cell Immune Function and Metabolism by Cellular Nutrient Sensor Mammalian Target of Rapamycin (mTOR) - Snyder, Julia P.; Amiel, Eyal (Frontiers in Immunology, 2019)
Dendritic cell (DC) activation is characterized by an acute increase in glucose metabolic flux that is required to fuel the high anabolic rates associated with DC activation. Inhibition of glycolysis significantly attenuates most aspects of DC immune effector function including antigen presentation, inflammatory cytokine production, and T cell stimulatory capacity. The cellular nutrient sensor mammalian/mechanistic Target of Rapamycin (mTOR) is an important upstream regulator of glycolytic metabolism and plays a central role in coordinating DC metabolic changes and immune responses. Because mTOR signaling can be activated by a variety of immunological stimuli, including signaling through the Toll-like Receptor (TLR) family of receptors, mTOR is involved in orchestrating many aspects of the DC metabolic response to microbial stimuli. It has become increasingly clear that mTOR’s role in promoting or attenuating inflammatory processes in DCs is highly context-dependent and varies according to specific cellular subsets and the immunological conditions being studied. This review will address key aspects of the complex role of mTOR in regulating DC metabolism and effector function.